PEMANFAATAN KARAGENAN DALAM PEMBUATAN SELAI LEMBARAN LABU KUNING (Cucurbita moschata) - Utari ' Pratiwi; Noviar Harun ' Harun; Evy ' Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objective of this research was to find the best concentrate of carrageenan on the chemical characteristics (water, ash, sucrose, and crude fiber content) and the sensory (color, flavor, taste, fineness, plasticity, and hedonic test) of pumpkin sheet jam. The experimental design used in this research was Completely Randomized Design (“CRD”) with four treatments, K1 (the addition of carrageenan 3.5% w/w), K2 (the addition of carrageenan 4.5% w/w), K3 (the addition of carrageenan, 5.5% w/w), and K4 (the addition of carrageenan 6.5% w/w). The result showed that the addition of carrageenan had an effect significant on the water, ash, sucrose, crude fiber content, the organoleptic test of taste, plasticity, and hedonic test. but did not significantly affect the organoleptic parameters of color, aroma, and smoothness. The selected pumpkin sheet jam was K4 which showed the concentrate of water, ash, sucrose, and crude fiber content were 24,25%, 1,13%, 50,60% and 2,08% respectively. Keywords: Carragenaan, pumpkin, sheet jam.